2020
DOI: 10.1002/ecs2.3004
|View full text |Cite|
|
Sign up to set email alerts
|

The Catalan butterfly monitoring scheme has the capacity to detect effects of modifying agricultural practices

Abstract: Citation: Lee, M. S., J. Comas, C. Stefanescu, and R. Albajes. 2020. The Catalan butterfly monitoring scheme has the capacity to detect effects of modifying agricultural practices. Ecosphere 11(1):Abstract. Impacts of agricultural management practices on the receiving environment are seldom suitably assessed because environmental monitoring is costly. In this regard, data generated by already existing environmental survey networks (ESNs) may have sufficient capacity to detect effects. Here, we study the capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…Research has indicated that seasons play a role in influencing the quantity and variety of insects present. It is also revealed that during the transition from short to long rains (January to March), we observed a higher number of butterfly species and a greater abundance of them than during the long to short rains transition that is April to June (Figure 5) These findings align with previous research conducted on Kihansi gorge, which found that butterfly species richness and abundance were higher during the dry season compared to other seasons [23].…”
Section: Seasonal Variation and Temporal Occurrence Of Butterflysupporting
confidence: 91%
“…Research has indicated that seasons play a role in influencing the quantity and variety of insects present. It is also revealed that during the transition from short to long rains (January to March), we observed a higher number of butterfly species and a greater abundance of them than during the long to short rains transition that is April to June (Figure 5) These findings align with previous research conducted on Kihansi gorge, which found that butterfly species richness and abundance were higher during the dry season compared to other seasons [23].…”
Section: Seasonal Variation and Temporal Occurrence Of Butterflysupporting
confidence: 91%
“…In the past century, Mediterreanean regions have been exposed to rapid rates of climate change (Serrano‐Notivoli et al ., 2018, 2019), as well as to contrasting pressures of rural depopulation and land abandonment, versus urbanisation, infrastructure development and agricultural intensification (Debussche et al ., 1999; Rescia et al ., 2010; Serra et al ., 2014; Herrando et al ., 2016). Over recent decades, Mediterranean butterfly communities have responded to climatic warming (Zografou et al ., 2014; Nieto‐Sánchez et al ., 2015) and drying (Herrando et al ., 2019), as well as vegetation encroachment (Ubach et al ., 2020) and changing agricultural practices (Lee et al ., 2020). Some evidence from these regional studies suggests that topographic variation or vegetation cover may counteract effects of climate change on insects (Nieto‐Sánchez et al ., 2015; Herrando et al ., 2019), as has been observed for Mediterranean bird communities (Clavero et al ., 2011; Barnagaud et al ., 2013; Tellería, 2019, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Butterflies are valuable environmental indicators because they rapidly and selectively respond even to subtle changes in habitat structure and climate [1,2] (and references therein). Their colorful appearance and aesthetic appeal have attracted attention to these insects from both the general public and decision-makers [3] and have made butterflies focal objects of multiple national and international monitoring schemes [4,5], as well as of citizen science projects (e.g., www.iNaturalist.org (accessed on 20 March 2021)). Because of this attention, butterflies are one of the best studied groups of insects-the Global Biodiversity Information Facility at the beginning of 2019 included over 7.5 million complete and unique records of butterflies from around the globe [6].…”
Section: Introductionmentioning
confidence: 99%